PENGARUH TERAPI AKTIVITAS KELOMPOK SOSIALISASI TERHADAP PENURUNAN TINGKAT KESEPIAN PADA LANSIA DI PANTI SOSIAL LANJUT USIA HARAPAN KITA PALEMBANG - Diana H.Soebyakto; Nuzula Firdaus; Malpin Saputra (Jurnal Kesehatan dan Pembangunan, 2026)
Reducing loneliness among the elderly has become a major challenge in improving their quality of life. One of the interventions that can help is socialization group activity therapy, which aims to reduce social isolation and increase interaction among the elderly. This study aims to analyze the effect of socialization group activity therapy on reducing loneliness levels in the elderly. The method used is an experiment with a pretest-posttest control group design. The research sample consisted of 30 elderly individuals, divided into two groups: the experimental group, which received socialization group activity therapy, and the control group, which did not receive any treatment. The measurement of loneliness levels was conducted using the UCLA loneliness scale before and after the therapy. The research results with a p-value of 0.000 < 0.05 indicate that there is an effect of socialization group activity therapy on the level of loneliness in the elderly. These findings indicate that socialization group activity therapy is effective in reducing loneliness levels in the elderly, which in turn can improve their quality of life.